2020
DOI: 10.3390/ijms21010353
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Chemical Study of Anthracene Selective Oxidation by a Fe(III)-Phenylporhyrin Derivative

Abstract: In this work, we studied the anthracene oxidation by hydroxyl radicals. Hydroxyl radical was generated by reaction of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin Fe (III) (TPPFe) with hydrogen peroxide under visible radiation at a nitrogen atmosphere. The TPPFe was synthesized by Adler Method followed by metal complexation with Fe (III) chloride hexahydrate. Hydroxyl radical was detected by fluorescence emission spectroscopy and we studied kinetic of anthracene selective oxidation by hydroxyl radicals throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Thematic Area 2 includes 22 articles, namely [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], the typification of which is shown in Table 3 . With some degree of conventionality, it is possible to subdivide the articles published here into two main groups, namely, articles devoted to the study of the kinetics of processes in which any chemical transformations are decisive, and articles devoted to the study of the kinetics of processes in which chemical transformations are either not decisive or absent altogether.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thematic Area 2 includes 22 articles, namely [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], the typification of which is shown in Table 3 . With some degree of conventionality, it is possible to subdivide the articles published here into two main groups, namely, articles devoted to the study of the kinetics of processes in which any chemical transformations are decisive, and articles devoted to the study of the kinetics of processes in which chemical transformations are either not decisive or absent altogether.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…With some degree of conventionality, it is possible to subdivide the articles published here into two main groups, namely, articles devoted to the study of the kinetics of processes in which any chemical transformations are decisive, and articles devoted to the study of the kinetics of processes in which chemical transformations are either not decisive or absent altogether. Among the articles of the first group, in turn, two categories can be distinguished, in the first of which are the clear majority; the processes related to them were considered in the articles [ 29 , 30 , 31 , 32 , 33 , 35 , 37 , 42 , 43 , 44 , 45 , 46 , 47 ]. For example, in [ 29 ], the kinetics of the aldol condensation of benzaldehyde and heptanal in liquid-phase systems using various solvents was characterized, and a very pronounced effect of the solvent was noted for a given set of identical kinetic parameters (i.e., the same kinetics of the liquid phase can lead to different values of conversion and yield of reaction products depending on the choice of solvent).…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…FLT is one of the most abundant PAHs in coal derivatives, such as creosote, and is found at many contaminated sites [ 26 ]. Considering the deleterious effects of PAH on human health and the environment, we have selected these four PAHs as the target of this study because they are some of the 16 priority PAHs indicated by the United States Environmental Protection Agency (UN-EPA) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…But peroxides tend to degrade, giving a plethora of sideproducts (Scheme 1). [29][30][31] Here we study the photochemical conversion of anthracene in the presence of titania-supported platinum SACs and compare this to supported platinum nanoparticles. We show that the SACs give higher conversion and maintain selectivity.…”
Section: Introductionmentioning
confidence: 99%